Using WSDM and Web Service Ping for QoS based Web Service Selection - Schoene, Thomas; Kaspar, Friedbert; Reich, Christoph (Electronic Communications of the EASST, 2009)
By using the standard Web Service Distributed Management (WSDM) and Web Service Ping, we introduce a lightweight solution to the Web Service QoS problem. The Management of Web Services (MOWS) part of WSDM is used to publish Web Service's QoS parameters. Management using Web Services (MUWS), the second part of WSDM, is used to monitor IT resources' QoS. Examples are server's QoS, application server's QoS and network's QoS. Web Service Ping can be used as a simple diagnostic tool for Web Service's latency and Web Service's availability across organizational boundaries. Therefore, we propose to introduce a standardized Web Service Ping operation into all Web Services. All QoS data retrieved by using MOWS, MUWS and Web Service Ping, can be used for Web Service selection. We introduced a new Web Service selection architecture, the Delegation Web Service as selector. Compared to Web Service Broker as selector, consumer as selector and QoS enhanced UDDI as selector, the Delegation Web Service as selector offers a better solution for implementing Web Service load balancing and can increase the security of and for Web Services.